Dose-Dependent Association of Gabapentinoids with Pulmonary Complications After Total Hip and Knee Arthroplasties. (5th February 2020) - Ohnuma, Tetsu; Raghunathan, Karthik; Moore, Sean; Setoguchi, Soko; Ellis, Alan R.; Fuller, Matthew; Whittle, John; Pyati, Srinivas; Bryan, William E.; Pepin, Marc J.; Bartz, Raquel R.; Haines, Krista L.; et al.
Abstract : Background: Gabapentinoids are commonly prescribed in perioperative multimodal analgesia protocols. Despite widespread use, the optimal dose to reduce opioid consumption while minimizing risks is unknown. We assessed dose-dependent effects of gabapentinoids on opioid consumption and postoperative pulmonary complications following total hip or knee arthroplasty (THA or TKA). We hypothesized that use of a gabapentinoid on the day of THA or TKA is associated with an increased risk of postoperative pulmonary complications in a dose-response fashion compared with the risk for patients who did not receive the drug. Methods: Using the Premier Database, we identified adults who underwent elective primary THA or TKA from 2009 to 2014. The exposure was receipt of a gabapentinoid (gabapentin or pregabalin) on the day of surgery. Gabapentin dose was categorized into 5 groups: none, 1 to 350, 351 to 700, 701 to 1, 050, and >1, 050 mg per day. Pregabalin dose was categorized into 4 groups: none, 1 to 110, 111 to 250, and >250 mg per day. The primary outcome was a composite of postoperative pulmonary complications, defined as respiratory failure, pneumonia, reintubation, pulmonary edema, noninvasive ventilation, or invasive mechanical ventilation. Results: Of 858, 306 patients who underwent THA or TKA, 11.0% received gabapentin and 10.2% received pregabalin. The mean age (and standard deviation) of the patients was 65.6 ± 10.7 years, 39.6% were male, 78.2% were Caucasian, and 55.2% were covered by Medicare. In multilevel regression analysis, receipt of gabapentinoid at any dose on the day of surgery was associated with increased odds of postoperative pulmonary complications. Compared with no exposure to the drug being used by the particular group, all dose ranges of gabapentin and pregabalin were associated with greater odds of postoperative pulmonary complications (odds ratio, 95% confidence interval = 1.51, 1.40 to 1.63, for >1, 050 mg of gabapentin and 1.81, 1.57 to 2.09, for >250 mg of pregabalin). We found no clinically meaningful associations between exposure to either gabapentin or pregabalin and perioperative opioid consumption or the length of the hospital stay. Conclusions: Exposure to gabapentinoids at any dose on the day of THA or TKA was associated with increased odds of postoperative pulmonary complications in a dose-response fashion, with minimal effects on perioperative opioid consumption. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.